Digitalization of the Energy Complex of the Republic of Belarus: State Analysis, Promising Areas, Alternative Proposal for Evaluating Efficiency - A. V. Tsedrik (Цифровая трансформация)
This article reflects a number of components that characterize the processes of digital transformation of the energy complex of the Republic of Belarus: costs for general activities, publication interest among industry specialists, the regulatory and legal basis for studying the ongoing process. A high degree of promotion of the state in terms of standardization and automation of energy in Belarus was also noted, including in comparison at the level of unification of the EAEU. A number of measures have been proposed in order to ensure the preselective functioning of the industry in the context of sanctions restrictions on the supply of equipment and software. The author proposes to conduct such an assessment, alternative to the indicators proposed in the Strategy of informatization and digital transformation of the state association of electric power industry «Belenergo» for the period of 2021–2025.